2021
DOI: 10.1021/acs.inorgchem.1c00078
|View full text |Cite
|
Sign up to set email alerts
|

Sr9Mg4.45(1)Bi9 and Sr9Mg4.42(1)Sb9: Mg-Containing Zintl Phases with Low Thermal Conductivity

Abstract: Zintl phases with nominal 9−4−9 formulas are very interesting for their potential applications as thermoelectric materials. However, the formation of such phases usually requires divalent transition metals, for example, Zn, Mn, and Cd, which are covalently bonded to the pnictogen atoms. In this report, for the first time, two Mgcontaining compounds with such structures as Sr 9 Mg 4.45(1) Bi 9 and Sr 9 Mg 4.42(1) Sb 9 were synthesized and their structures were determined by the single-crystal X-ray diffraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…7 Therefore, novel thermoelectric materials with high performance and a wide range of elements must be explored. [8][9][10][11][12] We observed that thermoelectric materials can be employed in daily life to meet the growing demand for energy. Highly efficient TE devices can generate electricity from heat waste.…”
Section: Introductionmentioning
confidence: 99%
“…7 Therefore, novel thermoelectric materials with high performance and a wide range of elements must be explored. [8][9][10][11][12] We observed that thermoelectric materials can be employed in daily life to meet the growing demand for energy. Highly efficient TE devices can generate electricity from heat waste.…”
Section: Introductionmentioning
confidence: 99%
“…However, substantial waste heat exists as low-grade energy near ambient temperature, and unfortunately, current commercial Bi 2 Te 3 -based thermoelectric materials, which are suitable to work in such a temperature range, are of low efficiency and high cost and severely limit massive applications . Therefore, exploration of new candidates, which are of high performance and composed of earth-abundant elements, will be especially meaningful. …”
Section: Introductionmentioning
confidence: 99%
“…Take Ca 1.84(1) Li 0.16(1) Zn 0.84(1) Sb 2 for example (Figure b), [ZnSb] layers are the basic unit of the anionic framework of the structure, propagating along the c -axial, wherein Ca 2+ (Li + ) are sandwiched between those layers. Notably, the Zn atom, which has a 4f site, is split by the (001) mirror plane, resulting in a disorder with a statistical site occupancy of ∼21%, similar to those interstitial sites in Sr 9 Mg 4+ x Pn 9 (Pn = Sb and Bi) and Ca 9 Mn 4+ x Sb 9 . , This structure can be regarded as a derivative of LiGaGe-type structure. The growth of high-quality single crystals of Ca 2 ZnSb 2 and Yb 2 MnSb 2 failed due to poor structural stability; yet, the successful preparation of Ca 1.84(1) Li 0.16(1) Zn 0.84(1) Sb 2 and Yb 1.82(1) Li 0.18(1) Mn 0.96(1) Sb 2 phases indicated the improved stability.…”
Section: Resultsmentioning
confidence: 93%